Analysis of Error in the Solution of the 2-D Diffusion Equation by Finite Element Methods - Moura, I.F.M.; Roumão, E.C.; Silva, J.B.C. (Trends in Computational and Applied Mathematics, 2008)
This work presents a numerical solution of the two-dimensional diffusion equation in comparison with the analytical solution. The norms L2 and L1 of the error are evaluated for two variants of the finite element method: the Galerkin Finite Element Method (GFEM) and the Least-Squares Finite Element Method (LSFEM). Two applications are presented and discussed.